Pemeriksaan dan Edukasi Keseimbangan untuk Mencegah Resiko Jatuh pada Masyarakat Pendekatan Single Leg Stance dan Time Up and Go - Astrid Komala Dewi; Catherine Hermawan Salim; Yurita Milintina (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
The risk of falls in the community in Kapuk Cengkareng Village, especially the elderly, is a health problem that can have a serious impact on quality of life. Balance examination and education are important preventive measures in reducing the risk of falls. This study aims to analyze the effectiveness of balance examinations using the Single Leg Stance (SLS) and Time Up and Go (TUG) methods and provide appropriate education to improve postural stability. The method used in this study involved balance tests with SLS and TUG in community groups with various age ranges. The data obtained were analyzed to see the relationship between balance test results and fall risk factors. In addition, balance education interventions were carried out including physical exercise and fall prevention strategies. There were 30 Respondents Involved in This Activity after the Task was completed The success measurement method was used to evaluate the pre- and Post-Test methods and N-Gain with a value of 0.9 indicating that the strength or category in this study was at a High Level. The calculation results showed a 70% increase from the Pre-test and Post-test results. This shows that respondents experienced positive changes after participating in the activity and that the Technique used could significantly improve the Results. The results showed that individuals with low scores on the SLS and longer travel times on the TUG had a higher risk of falling. The balance education provided was shown to improve balance ability and public awareness of fall risk factors. Thus, balance examination using the SLS and TUG methods and balance education can be an effective strategy in preventing the risk of falling in the community.